The Influence of Work Environment, Work Discipline and Motivation on Employee Performance at PT Tiki Jalur Nugraha Ekakurir (JNE) Amplas Trade Center Medan - Yovie Ernanda; Jusrin Efrata; Yossy Pratiwi; Trisafira Harahap; Hayanti Harefa (Institute of Computer Science (IOCS), 2022)
PT Tiki Jalur Nugraha Ekakurir (JNE) Amplas Trade Center Medan is one of the shipping companies in Indonesia. One of the most important factors in the development of PT Tiki Jalur Nugraha Ekakurir (JNE) Amplas Trade Center Medan is human resources. Based on employee performance data in 2019-2020, it shows a decrease in employee performance in the